Victorian Adventure Supplementary Reading Material - Roderick Hunt (Oxford Reading Tree, 2012)
This book is part of the phenomenally successful Oxford Reading Tree which is used to teach reading in 80% of primary schools. The stories within it are about much-loved Biff, Chip and Kipper, their friends and family, and the exciting adventures they have together.